Exploiting a silver–bismuth hybrid material as heterogeneous noble metal catalyst for decarboxylations and decarboxylative deuterations of carboxylic acids under batch and continuous flow conditions. Issue 13 (27th May 2021) - Mészáros, Rebeka; Márton, András; Szabados, Márton; Varga, Gábor; Kónya, Zoltán; Kukovecz, Ákos; Fülöp, Ferenc; Pálinkó, István; Ötvös, Sándor B.
Abstract : A silver-containing hybrid material is reported as a heterogeneous noble metal catalyst for protodecarboxylations and decarboxylative deuterations of carboxylic acids. Abstract : Herein, we report novel catalytic methodologies for protodecarboxylations and decarboxylative deuterations of carboxylic acids utilizing a silver-containing hybrid material as a heterogeneous noble metal catalyst. After an initial batch method development, a chemically intensified continuous flow process was established in a simple packed-bed system which enabled gram-scale protodecarboxlyations without detectable structural degradation of the catalyst. The scope and applicability of the batch and flow processes were demonstrated through decarboxylations of a diverse set of aromatic carboxylic acids. Catalytic decarboxylative deuterations were achieved on the basis of the reaction conditions developed for the protodecarboxylations using D2 O as a readily available deuterium source.